Analysis of Learning Objectives on the Biology Teacher Learning Implementation Plan at SMA Negeri 14 Gowa - Hamka Lodang; Muhiddin Palennari; Wahdaniah Wahdaniah (Biology Teaching and Learning, 2023)
Abstract. This descriptive study aims to determine: 1) the suitability of learning objectives with basic competencies (BC), 2) the distribution of cognitive process levels of learning objectives based on Bloom's taxonomy revision, and 3) the completeness of the components of the formulation of learning objectives in the lesson plan (LP) for high school biology teachers at SMA Negeri 14 Gowa. There were 11 LP studied, namely 6 LP for the even semester of class XI and 5 LP for the even semester of class XII for the academic year 2020/2021 which consisted of 22 BC, 80 indicators of competency achievement (ICA), and 80 formulations of learning objectives. The instruments used are assessment sheets and checklists. The data is processed by calculating the percentage (%) of each category. It was concluded: 1) the suitability of the learning objectives with the dominant BC (63.75%) was appropriate, 28.75% was quite suitable, and 7.50% was not suitable; 2) distribution of levels of cognitive process learning objectives based on the revision of Bloom's taxonomy dominant (53.75%) C2, each level has been represented but not proportionally; 3) the completeness of the dominant learning objective component (97.50) is incomplete, containing only audience and behavior components, some even have only behavior components.Keywords: lesson plans, learning objectives, suitability, distribution, completeness.